POLITIK HUKUM MAHKAMAH KONSTITUSI DALAM JUDICIAL REVIEW (SEBUAH PENDEKATAN SOSIOLOGIS) - Murdoko, Murdoko (Universitas Widya Mataram, 2020)
AbstractThe collapse of the New Order and the subsequent rise of the Reformation changed the political system, the legal system and the economic system. The political system and legal system almost all agree to change to become more liberal by promoting human rights, but for the economy there is division, which is to change to become liberal as in politics and law, and remain